Epigenetic age acceleration and neurotrophin signaling pathways in cancer-related cognitive impairment: a longitudinal, prospective cohort study - Sayer, Michael; Ng, Ding Quan; Trudeau, Julia; Chan, Raymond J.; Acharya, Munjal M.; Kober, Kord; Chan, Alexandre (Frontiers in Aging, 2025)
IntroductionBiological age acceleration and disruptions in neurotrophin pathway signaling may significantly contribute to cancer-related cognitive impairment (CRCI) etiology. In this study, we evaluated the relationship of epigenetic age acceleration with cognitive function measures and circulating BDNF levels. Furthermore, we evaluated DNA methylation (DNAm) patterns to explore neurotrophin pathway associations with CRCI symptoms.MethodsIn a longitudinal study, 51 newly diagnosed Adolescent and Young adult cancer patients and 8 age-matched healthy controls provided blood samples for DNAm and BDNF measurements with concurrent clinical assessments (#NCT03476070). We evaluated the relationship of epigenetic ageing with cancer status, circulating BDNF levels, and measured cognitive function. Next, we identified significant differentially methylated positions (DMPs), regions (DMRs), and significantly enriched pathways associated with BDNF and cognitive function outcomes.ResultsPhenoAge and GrimAge demonstrated significant age acceleration relative to non-cancer controls and worsening cognitive function symptoms, with accelerated GrimAge associated with decreasing BDNF levels. DMPs associated with 5 different cognitive function outcomes (FactCog Score, Response, Memory, Executive Function, Multi-Tasking) were mapped to genes within KEGG pathway HSA:04722 (Neurotrophin Signaling Pathway). Key enriched pathways relative to both subjective cognitive function and multiple objective cognitive measurement domains were also enriched with respect to BDNF levels, including Synapse (GO:0045202), Glutamatergic Synapse (GO:0098978), and Neuron Projection (GO:0043005).ConclusionCancer and cancer treatment lead to significant epigenetic age acceleration, which can influence neuronal health and CRCI symptom onset. Furthermore, DNAm patterns corroborate BDNF as a potential biomarker for CRCI and suggest neurotrophin pathways play a meaningful role in CRCI etiology.